Zimbabwe: Gukurahundi Victims’ Monologues, State Silences and Perpetrator Denials, 1987-2017 - Terence M. Mashingaidze (Babeș-Bolyai University, 2023)
The Zimbabwean government instigated Gukurahundi massacres resulted in the death of around 20 000 people. The majority of the victims belonged to the Ndebele ethnic group while the Fifth Brigade, a Shona dominated military outβit, were the main perpetrators of the mass killings. The atrocities ended with the signing of the Unity Accord of December 1987 between the ruling ZANU (PF) party, which had masterminded the atrocities, and the opposition (PF) ZAPU, whose supporters had borne the brunt of state highhandedness. After the cessation of hostilities the Zimbabwean government frustrated open conversations and public commemorations of the massacres. What conversations on Gukurahundi that took place were largely victims’ monologues. To interrogate this state instigated silencing of exposure and remembrance the article suggests an exigency for counter-narrating erasures of memories of harm and impunity. In the aftermath of massacres, I argue, harmed communities embolden themselves and coalesce their fractured senses of self by openly memorialising their collective suffering through open conversations about their shared victimhood, commemorations, and the assembling of monuments. The Robert Mugabe led government’s foreclosure of such avenues for public acknowledgements of mass injuries that are supposed to serve as visceral registers of what societies should remember to avoid in the future reveals its disregard for the wounded humanity of the constitutive political other. Thus, Gukurahundi as an historical episode reveals the pathology of mass harm silenced and rendered insignificant by the state.